Fructose Intake, Hypertension and Cardiometabolic Risk Factors in Children and Adolescents: From Pathophysiology to Clinical Aspects. A Narrative Review - Giussani, Marco; Lieti, Giulia; Orlando, Antonina; Parati, Gianfranco; Genovesi, Simonetta (Frontiers in Medicine, 2022)
Arterial hypertension, dyslipidemia, alterations in glucose metabolism and fatty liver, either alone or in association, are frequently observed in obese children and may seriously jeopardize their health. For obesity to develop, an excessive intake of energy-bearing macronutrients is required; however, ample evidence suggests that fructose may promote the development of obesity and/or metabolic alterations, independently of its energy intake. Fructose consumption is particularly high among children, because they do not have the perception, and more importantly, neither do their parents, that high fructose intake is potentially dangerous. In fact, while this sugar is erroneously viewed favorably as a natural nutrient, its excessive intake can actually cause adverse cardio-metabolic alterations. Fructose induces the release of pro-inflammatory cytokines, and reduces the production of anti-atherosclerotic cytokines, such as adiponectin. Furthermore, by interacting with hunger and satiety control systems, particularly by inducing leptin resistance, it leads to increased caloric intake. Fructose, directly or through its metabolites, promotes the development of obesity, arterial hypertension, dyslipidemia, glucose intolerance and fatty liver. This review aims to highlight the mechanisms by which the early and excessive consumption of fructose may contribute to the development of a variety of cardiometabolic risk factors in children, thus representing a potential danger to their health. It will also describe the main clinical trials performed in children and adolescents that have evaluated the clinical effects of excessive intake of fructose-containing drinks and food, with particular attention to the effects on blood pressure. Finally, we will discuss the effectiveness of measures that can be taken to reduce the intake of this sugar.